Vzklitje slovenskega umetnostnozgodovinskega izrazja - Dolšina, Marjana (Jezik in slovstvo, 2015)
The formation of professional terminology is a prerequisite for the consolidation and development of any scientific discipline. It represents an essential tool for the dissemination of theoretical knowledge. The very first efforts to create the terminology of Slovenian art history can be traced back to the last quarter of the 19th century. The groundbreaking work Building Styles) (Stavbinski slogi) was accomplished by priest and art historian Janez Flis. It contains a comprehensive overview of the development of architecture, while at the same time offering a wide range of Slovenian terminological expressions related to the field, accompanied by the established terms from foreign languages, mainly German. An analysis of the vocabulary relating to gothic vaulting systems reveals the state of terminology in Slovenian art history in the initial phase of its development, before it became established as an academic discipline and was formally acknowledged by the opening of a new department at the University of Ljubljana in 1919.
Keywords: Flis, Janez, 1841-1919; "Stavbinski slogi"; Slovene; slovenščina; terminologija; terminology; znanstveni jezik; art history; umetnostna zgodovina; architecture; arhitektura; duhovniki; umetnostni zgodovinarji; 19./20. st.